2013
DOI: 10.1016/j.jnucmat.2013.01.263
|View full text |Cite
|
Sign up to set email alerts
|

Ion energy measurements on MAST using a midplane RFEA

Abstract: Ion energy measurements have been made in the scrape off layer of the Mega Amp Spherical Tokamak (MAST) using a midplane retarding field energy analyser (RFEA) in H-mode plasmas during the inter-edge localised mode (ELM) period and during type I and type III ELMs. During the inter-ELM period at distances of 3 to 8 cm from the last closed flux surface (LCFS), ion temperatures of 20 to 70 eV have been measured giving an ion to electron temperature ratio of 2 to 7 with a mean of 4. During type III ELMs, an ion te… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…1, a collection of T i /T e measurements from a number of tokamak SOL has been examined for measurements taken before 2010, showing values that range from the lower T i /T e $ 1 to the extreme T i /T e $ 10, with most of the data falling between 1 and 4. More recent measurements, in HL-2A, 3 in MAST, 2,4 in Alcator C-MOD, 7,8 and in ASDEX Upgrade 6 have confirmed these findings. The ion temperature is therefore usually higher than the electron one in the SOL.…”
Section: Introductionmentioning
confidence: 54%
“…1, a collection of T i /T e measurements from a number of tokamak SOL has been examined for measurements taken before 2010, showing values that range from the lower T i /T e $ 1 to the extreme T i /T e $ 10, with most of the data falling between 1 and 4. More recent measurements, in HL-2A, 3 in MAST, 2,4 in Alcator C-MOD, 7,8 and in ASDEX Upgrade 6 have confirmed these findings. The ion temperature is therefore usually higher than the electron one in the SOL.…”
Section: Introductionmentioning
confidence: 54%
“…Uncertainty in α LP , given in equation 2, arrises from uncertainty in T i /T e . Previous measurements on MAST have shown that 1 ≤ T i /T e ≤ 2.5 is reasonable for L-mode conditions [26][27][28] .This then gives α LP = 2.7 ± 0.1. Since α BP P cannot be measured directly in the system described in this paper the empirical value of α BP P = 0.6 ± 0.3 6,10,12,14 found across a number of experiments is adopted.…”
Section: Electron Temperature Measurementsmentioning
confidence: 78%
“…Figure 6 shows the profile of α LP obtained with this technique in each shot. In these calculations T i = 2T e was assumed, which is motivated by previous measurements on MAST [26][27][28] . Figure 6 shows that the secondary electron emission can have a major impact on the calculation of α LP .…”
Section: Electron Temperature Measurementsmentioning
confidence: 99%
“…These measurement techniques, which have been used on MAST at the mid-plane [5] [6] and at the divertor [7], operate on timescales slower than the ELM event and therefore do not give any information on the evolution of the temperature during the ELM rise and fall as seen in both deuterium alpha (D α ) light at the mid-plane and current signals measured by electrical probes such as Langmuir probes (LP). A new measurement technique and associated analysis method has been employed on MAST using the divertor RFEA which allows measurements within the time during which ions from the ELM arrive at the target.…”
Section: Introductionmentioning
confidence: 99%